Evaluating Simulation-Based Tobacco Treatment Scenarios for Providers Delivering Treatment for People Living With Mental Illnesses - Okoli, Chizimuzo T. C.; Otachi, Janet K.; Seng, Sarret; Abufarsakh, Bassema; Williams, Lovoria B. (Frontiers in Psychiatry, 2022)
Background: People living with mental illnesses (PMI) experience elevated tobacco use and related morbidity and mortality. Despite the availability of effective and safe tobacco treatments along with evidence that PMI are motivated and able to quit successfully, few Mental and behavioral healthcare providers (MHPs) engage PMI in such treatment. MHPs may lack the confidence or skills to engage their clients in tobacco treatment. Currently, there are limited training modalities to prepare MHPs in delivering tobacco treatment for PMI. However, animated scenario-based simulated encounters can bridge this gap to effectively provide tailored MHP training to enhance treatment delivery. Hence, the purpose of this study was to evaluate simulated tobacco treatment education scenarios tailored to MHPs Methods: For this evaluation, we used a pretest-posttest design to assess changes in MHPs tobacco treatment knowledge and behavioral intentions after viewing simulated treatment encounters. We developed four animated scenarios, using brief tobacco treatment interventions, simulating treatment encounters with PMI. MHPs were primarily recruited from mental or behavioral healthcare facilities and were asked to complete a web-based questionnaire. Their knowledge, views, and experiences in providing tobacco treatment were assessed prior to viewing the animated scenarios. Participants were then asked to evaluate the desirability, acceptability, and applicability of the animated scenarios; and thereafter, their knowledge of and intentions to provide evidence-based tobacco treatment were again assessed. Results: Participants (N=81) were on average 41.0 years of age, mostly female (79.0%), and non-Hispanic White (86.4%). Nearly a quarter endorsed current tobacco use and few had tobacco treatment training (14.8%). Overall knowledge of tobacco treatment scores significantly increased before and after viewing the videos (M=3.5 [SD=1.0] to M=4.1 [SD=1.0], p<.0001). After viewing the simulated scenario videos, participants endorsed moderate to high mean scores (ranging from 4.0-4.2 on a 0 to 5 scale) on the desirability, acceptability, and applicability of the different animated scenarios and intention to provide tobacco treatment. Conclusions: These findings suggest that the use of brief animated scenarios may be a useful modality to enhance MHPs knowledge acquisition and treatment delivery intentions. Such approaches may be integrated into tobacco treatment trainings for MHPs.